Evidence for local inflammation in complex regional pain syndrome type 1 - Frank J. P. M. Huygen; Anke G. J. de Bruijn; Martha T. de Bruin; J. George Groeneweg; Jan Klein; Freek J. Zijlstra (Mediators of Inflammation)
Background: The pathophysiology of complex regional pain syndrome type 1 (CRPS 1) is still a matter of debate. Peripheral afferent, efferent and central mechanisms are supposed. Based on clinical signs and symptoms (e.g. oedema, local temperature changes and chronic pain) local inflammation is suspected.